O discurso violento em comentários online: interações no jornal Folha de São Paulo no Facebook - Silva, Lee Jefferson Pontes da (2019)
The objective of this dissertation was to analyze and describe the violent discourse manifested in the form of an online commentary in publications of the Folha de São Paulo newspaper in fanpage on Facebook. This objective is based on the concepts society, discourse and cognition coming from the perspective of the cognitive theory of strategic information processing (VAN DIJK 1983b, 1984a, 2004, 2005, 2006, 2008, 2011, 2016a and 2016b), sociocognitive discourse theory (HAMILTON, 1981a; TAJFEL, 1981, 1982) and the theory of social cognition (ARGYLE, FURNHAM, & GRAHAM, 1981; FORGAS, 1979, 1981; FURNHAM & ARGYLE, 1982; VAN DIJK, 1983). The methodology that guided the achievement of the above mentioned objective is of a qualitative and interpretative nature, being based on an ethnographic case study approach, because we can describe the culture involved in the production of hate speech that has gained space in the virtual environment, thus, this research aims to describe the behavior of social actors and the meanings that the online enunciators attribute to discursive acts and virtual interactions (SPRADLEY, 1979). By means of this methodological aim, we generated a corpus of 696 online comments, that were collected at Folha de São Paulo's Facebook Fanpage, which were analyzed through the techniques of the Linguistic-Sociocognitive Model (VAN DIJK, 2016a) and the Systems of Beliefs and Social Mental Models (VAN DIJK, 2016b). The results found allow us to reach the conclusion that the semantic and cognitive models constructed by the technosocial actors in the posts of Folha de São Paulo act expressively and/or significantly in the orientation of the formulation of online comments. Based on these findings, we can state that the belief systems and context conditions guide both the positioning and the orientation of the construction of the senses in online comments.